Dynamic Properties and Dynamic Response Model of Jointed Granites by Cyclic Loading - Ding, Xiaobin; Zhao, Junxing; Dong, Yaojun (Advances in Civil Engineering, 2024)
The present study investigates the dynamic properties of granite samples with varying degrees of defects through triaxial cyclic loading experiments conducted under different conditions, including varied confining pressures, loading frequencies, dynamic stress amplitudes, and number of cycles, and the dynamic response model of granite samples influenced by the confining pressure and frequency are constructed. The results show that the dynamic elastic modulus of granite increases, but its dynamic damping ratio decreases as the confining pressure increases. The dynamic elastic modulus and dynamic damping ratio of the granite increase as increasing frequency. The dynamic elastic modulus of granite increases with the increasing dynamic stress amplitude while its dynamic damping ratio decreases. The dynamic elastic modulus and dynamic damping ratio of granite decreases with an increasing number of cycles. The modified Duncan–Chang model can well describe the dynamical behavior of granite influenced by the confining pressure and frequency. The correlation coefficients of the modified model reached 0.98. It is worth saying that the correlation coefficient of the model is low at 20 Hz frequency. It indicates that frequency has a strong effect on the dynamic response of granite compared with the confining pressure. These data and models will be applied to the next step of detection and prediction of the tunnel rock stress state.